2014
DOI: 10.1016/j.chb.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Giving and receiving emotional support online: Communication competence as a moderator of psychosocial benefits for women with breast cancer

Abstract: This study examines the moderating role of emotional communication competence in the relationship between computer-mediated social support (CMSS) group participation, specifically giving and receiving emotional support, and psychological health outcomes. Data were collected as part of randomized clinical trials for women diagnosed with breast cancer within the last 2 months. Expression and reception of emotional support was assessed by tracking and coding the 18,064 messages that 236 patients posted and read i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 78 publications
4
88
0
7
Order By: Relevance
“…Apart from intensity of online participation, patients also differ on aspects outside the online environment, which may affect online behavior and effectiveness of online support group participation as well. For example, recent studies suggest that individual differences in health self-efficacy [ 18 ], emotional communication competence [ 19 ], and differences in coping with emotions [ 20 ] might be moderating factors. In this study, we focus on patients’ level of emotional approach coping (ie, actively processing and expressing emotions).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from intensity of online participation, patients also differ on aspects outside the online environment, which may affect online behavior and effectiveness of online support group participation as well. For example, recent studies suggest that individual differences in health self-efficacy [ 18 ], emotional communication competence [ 19 ], and differences in coping with emotions [ 20 ] might be moderating factors. In this study, we focus on patients’ level of emotional approach coping (ie, actively processing and expressing emotions).…”
Section: Introductionmentioning
confidence: 99%
“…The reiteration of one ordeal, the effort to overcome it and the knowledge shown from explaining medical terms hinted the emotional communication competence. Participants with emotional communication competence might felt self-efficacy by being able to provide support to other women (through her experience) (Yoo et al, 2014). Women who participated in this group can be considered as in the effort of finding answers and gaining support that might otherwise receive from their offline surrounding.…”
Section: Understanding the Message Through Informal Languagementioning
confidence: 99%
“…The InfoTrend system has been utilized for analyzing news media coverage across diverse areas, such as information management business, government projects (Bengston, Potts, Fan, & Goetz, 2005), and academic research (Fan et al, 2001; Jasperson, Shah, Watts, Faber, & Fan, 1998; Shah et al, 2002). Recently, this program has been successfully applied to analyze natural language used in online social support groups (Han et al, 2011; Kim et al, 2011; Namkoong et al, 2010, 2013; Yoo et al, 2014). …”
Section: Content Codingmentioning
confidence: 99%
“…If there are multiple waves of data collection, message production and consumption can be calculated based on the intervening time period and integrated into the survey data on that basis (Yoo et al, 2013). Merging survey data into the content coding and action log data sets, more specifically, researchers have investigated the psychological benefits of emotional and informational support expression and reception occurring within CMSS groups for breast cancer patients (Han et al, 2011; Namkoong et al, 2010, 2013; Yoo et al, 2014). For example, Namkoong et al (2013) found that expression, but not reception, of emotional support increases cancer patients’ perceived bonding with other patients in CMSS groups, which in turn mediates the effects on positive coping strategies.…”
Section: Merging Survey Data Into the Coding/log Datamentioning
confidence: 99%
See 1 more Smart Citation